PEMANFAATAN AMPAS SALAK BALI MENJADI MANISAN KERING - Leni Meiliyani .; Ni Desak Made Sri Adnyawati, S.Pd,M.Pd .; Ni Made Suriani, S.Pd, M.Par. . (Jurnal BOSAPARIS: Pendidikan Kesejahteraan Keluarga, 2015)
Penelitian ini bertujuan untuk (1) mengetahui resep manisan kering ampas salak Bali (2) kualitas manisan kering ampas salak Bali dari aspek tekstur dan aspek rasa. Peneltian ini merupakan penelitian eksperimen dengan teknik pengumpulan data menggunakan metode observasi. Data dianalisis menggunakan teknik deskriptif kualitatif dan deskriptiif kuantitatif. Uji panelis melibatkan panelis terlatih sebanyak 25 orang.Hasil penelitian manisan kering ampas salak Bali menunjukkan (1) resep manisan kering ampas salak Bali terdiri dari 200 gr ampas salak Bali, 200 gr gula pasir, 50 gr tepung tapioka, 6 sdm (35 ml) air asam Jawa. Proses pengolahan dilakukan dengan mencuci dan merendam ampas salak Bali selama 1 Jam. Ampas salak yang telah diblender, di masukkan kedalam larutan gula pasir dengan menambahkan air asam Jawa, sambil diaduk selama 1 jam masukka tepung tapioka sedikit demi sedikit hingga matang. Diamkan satu malam kemudian adonan ditimbang seberat 5 gram dan dibentuk sesuai selera. Proses pengeringan tahap 1 selama 2 jam, selanjutnya tahap 2 manisan dikeringkan kembali selama 5-6 hari. Proses pengemasan dilakukan menggunakan plastik bening dan pita kawat, hasil manisan kering ampas salak Bali 54 biji. (2) kualitas manisan kering ampas salak Bali dari aspek tekstur berada dalam kategori baik dengan skor (2,76). Kualitas manisan kering ampas salak Bali dari aspek rasa berada dalam kategori baik dengan skor (2,68). Kata Kunci : ampas salak Bali, manisan kering, kualitas This study aimed to (1) know the recipe of dried candies which were made from Bali snake fruits’ pulp, and 2) the quality of dried candies which were made from Bali snake fruits’ pulp from the texture and taste aspects. This study was an experimental study and observation method was the instrument for data collection. The obtained data were analyzed using both of qualitative and quantitative descriptive technique. The test involved 25 trained panalists. The results of this research showed that 1) dried candies which were made from Bali snake fruits’ pulp made of 200 grams of Bali Snake fruits’ pulp, 200 grams of sugar, 50 grams of starch, and 6 tbsp (35 ml) of tamarind. The process of making the dried candies was firstly, washed and submerged the Bali snake fruits’ pulp for one hour. Secondly, the Bali snake fruits’ pulp which was blended, then put into sugar solution which have been added with tamarind. Next, stirred it for one hour, and then added the starch little by little until the mixture cooked. Thirdly, wait until a night, then, the mixture weighing 5 grams was shaped personalizing. Next, it was about the process of desiccation. The first step of the process of desiccation was for two hours, and then the second step was for five to six days. The last is about the packing process. The packing procces was done by using clear plastic and wire ribbon. The candies that were produced were 54 candies. (2) the quality of dried candies which were made from Bali snake fruits’pulp in the aspect of the textures was in good category with score of (2,76). The quality of dried candies which were made from Bali snake fruits’pulp in the aspect of the taste was in good category with score of (2,68). keyword : Bali snake fruits’ pulp, dried candies, quality.